Assessing and quantifying the secure base script from narratives produced by preschool age children: justification and validation tests - Vaughn, Brian E. (2019)
Building on aframework presented by Bretherton and associates, Waters and associates argued that interaction sequences relevant to children's access to and use of asecure base for exploration during infancy/toddlerhood become internalized as script-like representations. For adults, these scripted representations are readily assessed using word-prompt lists d to elicit attachment relevant narratives. However, this method is not appropriate during early childhood. Waters and associates used stories from Bretherton's Attachment Story Completion Task for this purpose. However, the method they used to score secure base script use is not efficient for larger samples (e.g. over 50), and new approaches for scoring have been designed. We describe two approaches to story selection and scoring for access to and use of the secure base script. The two scoring methods show substantial and significant overlap and also have significant associations with other methods of measuring attachment security during early childhood.